Terrorismo, immigrazione e annullamento dell’identità umana - Francesco Fargnoli; Domenico Fargnoli (Il sogno della farfalla, 2018)
In the last few years, a thought has spread – which has been amplified by the media and social networks – according to which there is a correlation between immigration and terrorism. The several different studies that have been run on the topic have shown that there is not such a link. Rather, there exists a correlation between colonial and neo-colonial policies and the growing conflict between different cultures. Possibly, it is not a coincidence that, prior to the Gulf war, terrorist attacks occurred at a lower rate and then progressively increased in the following years. Moreover, the Countries where most terrorist attacks take place are those whose foreign policies basically consist in new forms of colonialism (the USA, France, and the UK). Psychiatry has somehow aligned itself with this way of thinking, ignoring completely the effects the loss of human rights due to new colonial policies has on people.